EXAMINING THE IMPACT OF COMPETENCE, JOB SATISFACTION, AND ORGANIZATIONAL COMMITMENT ON EMPLOYEE PERFORMANCE: A CASE STUDY OF THE MENGWI VILLAGE OFFICE IN BADUNG REGENCY - Renata, I Putu Dida; Kusuma, I Gusti Ngurah Agung Gede Eka Teja; Permadi, I Komang Oka (EMAS, 2025)
Human resources play a very important role in the existence of an organization. Prospective assets, human resources can be transformed into real potential, both tangible and intangible. This study aims to determine how organizational commitment, job satisfaction, and employee competence influence employee performance at the Mengwi Village Office in Badung Regency. The study was conducted at the Mengwi Village Office in Badung Regency. The entire population of 33 Mengwi Village Office employees in Badung Regency was used as the research sample. Thus, census-based research was conducted using the entire population as the sample. Data was collected through questionnaires, interviews, and observations. Multiple linear regression analysis was conducted using SPSS version 26 software. According to the results of the analysis, employee performance at the Mengwi Village Office in Badung Regency is positively and significantly influenced by employee competence. Employee performance at the Mengwi Village Office increases with increasing competence. Employee performance at the Mengwi Village Office is positively and significantly influenced by job satisfaction. Employee performance at the Mengwi Village Office will increase with increased job satisfaction. Employee performance at the Mengwi Village Office in Badung Regency is also positively and significantly influenced by organizational dedication. Employee performance will increase with increasing organizational commitment.